IMPORTANCE OF GAMES IN TEACHING ENGLISH IN PRESCHOOL EDUCATION - Naurizbayeva Arzayim Bakhtiyarovna (Journals Park Publishing, 2023)
Preschool education lays the foundation for a child's future academic success and language development. When it comes to teaching English to young learners, incorporating games into the curriculum is not just a fun diversion but a powerful educational tool. This article explores the significance of games in preschool English education, shedding light on how play-based activities foster language acquisition, creativity, and a positive attitude towards learning.
Keywords: Preschool education, English language acquisition, educational games, global perspectives, multilingual competence, cultural sensitivity, inclusivity, language as a bridge, international experiences, globalized future.